Pengaruh Opini Audit, Pergantian Manajemen, Ukuran KAP, Ukuran Perusahaan Klien, dan Financial Distres Terhadap Auditor Switching Voluntary (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Sara, Beta Yuni, Drs. Atwal Arifin, M.Si., Akt (2017)
This study aimed to examine the factors that affect the auditor switching voluntarily. Variables that considered to affect are audit opinion, management changes, KAP size, client size, and financial distress. The populations in this study are all manufacturing companies listed in Indonesia Stock Exchange, period 2010-2015. The methods used to determine sample is purposive sampling. Based on those criteria, 120 companies acquired during six years of observation. Data analysis technique used is logistic regression analysis. The result of the study showed that KAP size affect to the auditor switching voluntary. Audit opinion, management changes, client size, and financial distress has no affect to the auditor switching voluntary.